Evaluation of the seismic vulnerability of the buildings in the urban area of the district Chiquian, using the ArcGIS model builder - Tinoco Meyhuay, Tito (2019)
The present descriptive, non-experimental and transversal investigation work has theobjective of evaluate the seismic vulnerability of the buildings of the urban area of thedistrict of Chiquian applying the AcrGIS model builder.The proposed methodology allows the automation and the creation of a model ofseismic vulnerability using the ArcGIS model builder, where eleven parameters wereevaluated for the determination of the vulnerability index and the damage index in thebuildings of the urban area of the district of Chiquian.Of an overall of 1417 buildings, it was found that the 14,7% of the houses are in lowvulnerability, the 21% in medium vulnerability, the 48,8% in high vulnerability andthe 15,2% in very high vulnerability. Besides, considering the vulnerability index anda horizontal acceleration of the ground of 0,32 g, it was calculated that 1209 houses(85,32%) suffered the total collapse and 208 houses (14,68%) will keep standing withsome structural damage. According to the index of calculated damage and consideringthe price per square meter of building, if an earthquake would occur, with thepreviously described characteristics